Peningkatan Pengetahuan Remaja tentang Pernikahan Dini sebagai Faktor Risiko Stunting - I Made Sudarta; Iqra S Iqra S; Yasirul Muntaha (STIKES Marendeng Majene, 2026)
Marriage is a socially and legally recognized union between two individuals regarded as partners. Early marriage remains a persistent issue in West Sulawesi, including in Mamuju, where its prevalence continues to be high and is accompanied by elevated stunting rates. This situation underscores the need for collective attention and coordinated action from all stakeholders to reduce both early marriage and stunting. The low level of adolescents’ knowledge regarding the impact of early marriage on stunting served as the basis for implementing this community service activity. The purpose of this program was to enhance adolescents’ understanding of early marriage as a risk factor for stunting. The activity was carried out at SMAN 3 Mamuju. An increase in participants’ knowledge about early marriage and stunting was observed following the educational intervention. It is expected that the students will take part in efforts to reduce the prevalence of early marriage, particularly in Mamuju.